Establishing the Logos of Melissus: A Note on Chapter 1, Hippocrates’ De natura hominis - Harriman, Benjamin (Revista Archai, 2021)
The earliest mention of Melissus of Samos by name is found in the first chapter of the Hippocratic De natura hominis. In the following note, I attempt to examine what is meant by the reference Melissus’ ‘logos’ in this work and suggest, against previous accounts, including Galen’s, that it has little to do with his commitment to monism. Rather Melissus’ logos is better understood as his referring to his strategy for demonstrating such a conclusion, especially his use of a supplemental argument in his fragment B8. Polybus’ concern in this first chapter is not monism as such but the claims to knowledge monists make. Melissus is a prime example of a monist who fails to grasp what he claims to know.